Ag+, Fe3+ and Zn2+-intercalated cadmium(ii)-metal–organic frameworks for enhanced daylight photocatalysis. Issue 81 (3rd November 2017) - Surib, Nur Atiqah; Sim, Lan Ching; Leong, Kah Hon; Kuila, Aneek; Saravanan, Pichiah; Lo, Kong Mun; Ibrahim, Shaliza; Bahnemann, Detlef; Jang, Min
Abstract : A new generation MOF photocatalyst capable of harvesting day light was fabricated by intercalating chosen metal ions onto a Cd(ii ) metal–organic framework. Abstract : Design and synthesis of multi-dimensional metal–organic frameworks are fascinating because MOFs possess intriguing structures and unique properties and exhibit potential applications in photocatalysis. In the present study, we endeavoured to synthesize a new Cd-linked MOF through a simple hydrothermal route. The daylight utilising attributes of the Cd-MOF were enhanced by intercalating Ag +, Fe 3+, and Zn 2+ into the framework via an ion-exchange technique. The optical property shows that Fe 3+ stimulates the photo response in the visible region, whereas Ag + and Zn 2+ stimulate the photo response in the ultraviolet light region. Photocatalytic efficiency of the developed MOFs was investigated by degradation of 2-CP under daylight illumination. The Cd-MOFs intercalated with Fe 3+ exhibit excellent photocatalysis as compared to the rest, degrading 93% of 2-CP in 5 h of illumination. The intercalation of Fe 3+ onto the Cd-MOF significantly reduced the energy gap of the pure MOF; this led to an increased formation of reactive oxygen species driven by the electrons (e − ) and holes (h + ). Thus, the developed modified MOF clearly demonstrated its capability as a daylight photocatalyst as compared to the existing conventional photocatalysts.